Development of a nutrition bar using pili nuts (canarium ovatum) and malunggay powder (moringa oleifera) - Garcia, Francis Anton S. (College of Home Economics, University of the Philippines Diliman, 2023)
The study developed a nutrition bar product that utilizes the untapped commercial and economic potential of pili nuts (PN) and applies the proven nutritional value of the malunggay. Three (3) nutrition bar prototypes based on reviewed recipes were modified by substituting nut ingredients with PN and adding malunggay powder (MP) to improve nutritive properties of the product. Sample prototypes were subjected to visual sensory evaluation via consumer acceptability using the 9-point hedonic scale and nutritional value assessment through proximate analysis. Hedonic scores obtained for the three prototypes ranged from 4.34 (“dislike slightly) to 6.89 (''like moderately”) based on color, sheen, heterogeneity, overall appearance, elasticity, binding and overall texture. Visual sensory results for the three products all scored significantly lower (p<0.05) compared to the control sample although all attribute scores for the most acceptable prototype were able to reach the 5.50 baseline threshold with the exception of color rating. Low hedonic scores for the prototypes were mainly attributed to the negative perception of the green color imparted by MP. In terms of nutrition, all prototypes generally have macronutrient profiles similar to those of commercially available product counterparts. Substitution of peanuts or cashews with PN resulted in products with generally higher fat content and production cost (₱40.59 - ₱72.19 projected increase in ingredient expenses). The PN and MP nutrition bar could potentially serve as a nutritious albeit more expensive alternative to locally accessible nutrition bar products. Further optimization of the designed prototype could include reformulation based on respondent preferences, mixture design testing and further nutritive analysis of fiber, vitamin and mineral content.